2009
DOI: 10.1038/nrn2647
|View full text |Cite
|
Sign up to set email alerts
|

Neural regulation of endocrine and autonomic stress responses

Abstract: Preface The survival and well-being of all species requires appropriate physiological responses to environmental and homeostatic challenges. The reestablishment and maintenance of homeostasis entails the coordinate activation and control of neuroendocrine and autonomic stress systems. These collective stress responses are mediated via largely overlapping circuits in the limbic forebrain, hypothalamus and brainstem, so that the respective contribution of the neuroendocrine and autonomic systems is tuned in acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

48
2,223
0
53

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,589 publications
(2,402 citation statements)
references
References 194 publications
48
2,223
0
53
Order By: Relevance
“…These autonomic changes are generated and regulated by evolutionarily conserved brain areas 9, 10, 11. Collectively, these areas are referred to as a “central autonomic network” or, more inclusively, as brain areas for visceral control 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…These autonomic changes are generated and regulated by evolutionarily conserved brain areas 9, 10, 11. Collectively, these areas are referred to as a “central autonomic network” or, more inclusively, as brain areas for visceral control 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the evidence showing that the PFC regulates the activity of the HPA axis [2,10], previous studies had reported conflicting results regarding the role of the medial PFC on basal plasma levels of corticosterone [5,6] probably because they did not distinguish well the prelimbic and infralimbic parts of the medial PFC. As shown, the stimulation of infralimbic cortex by local injections of picrotoxin increased the basal concentrations of corticosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Yet how the PFC exerts this regulation is a matter of debate. Previous studies in rodents suggest that the dorsal (prelimbic) and ventral (infralimbic) parts of the medial PFC exert opposite control on the HPA axis activity and plasma levels of corticosterone in response to stress [2][3][4]. However, most pharmacological and lesion studies are limited to the dorsal part of the medial PFC or do not distinguish between the dorsal and ventral parts [5][6][7][8] and, therefore, the role played by the infralimbic cortex in the regulation of the HPA axis and corticosterone concentrations is still uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress activates neuroendocrine systems and affects the activity of the relative brain area, causing physiological and behavioral responses (Chrousos, 2009; Ulrich‐Lai & Herman, 2009). The most commonly activated neuroendocrine system is the hypothalamus–pituitary–adrenal (HPA) axis, which plays important roles in the response to stressful conditions (Herman et al., 2003; Lupien, McEwen, Gunnar, & Heim, 2009).…”
Section: Introductionmentioning
confidence: 99%